Capability Component of Fraud and Fraud Prevention in the Saudi Arabian Banking Sector - Baz Rayaan; Rose Shamsiah Samsudin; Ayoib Che-Ahmed; Oluwatoyin Muse Johnson Popoola (International Journal of Economics and Financial Issues, 2016)
Fraud is a fundamental problem with every financial institution in the world, and Saudi Arabian banking sector is not immune to this malaise. Advances in technology that have led to the development of electronic banking have created new challenges for preventing fraud in the banking sector. This study develops a conceptual framework that can be used by banks in Saudi Arabia to prevent fraud in light of the capabilities of bank staff to perpetuate fraud. The respondents of this study are personnel in different managerial level in the Saudi Arabian banking sector. However, the limitation of the study is that it targets banking personnel in Saudi Arabia only. As an expectation, there will be a positive relationship between capability component of fraud and bank-related fraud prevention in the Saudi Arabian banking sector.